2018
DOI: 10.1111/ens.12294
|View full text |Cite
|
Sign up to set email alerts
|

Simulation study to determine why only some termites are active during tunneling activity

Abstract: It has been known that some termites are responsible for tunnel excavation for foraging, while others are not involved in the excavation. The biological reason for this is that the resting termites are a backup for the termites that have used up their energy in the tunneling activity. In this study, we build an agent‐based model (ABM) wherein agents (simulated termites) follow simple rules that govern their behavior. In this model, the agents are endowed with a directional vector that has been shown to exist i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…This may reflect their habitats, where H. aureus is found in deserts with cactus resources that are small and relatively difficult to find, while R. tibialis lives in pine forest with large wood resources. However, other factors including colony size and traveling cost also determine search efficiency [32,33]. We found that the behavioral mechanism underlying this adaptation is simple, where the tunnel geometry is sensitive to a single behavioral parameter governing interactions; namely, a threshold for individuals in a clogged tunnel to excavate a sidewall instead of waiting for access to the tunnel face.…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect their habitats, where H. aureus is found in deserts with cactus resources that are small and relatively difficult to find, while R. tibialis lives in pine forest with large wood resources. However, other factors including colony size and traveling cost also determine search efficiency [32,33]. We found that the behavioral mechanism underlying this adaptation is simple, where the tunnel geometry is sensitive to a single behavioral parameter governing interactions; namely, a threshold for individuals in a clogged tunnel to excavate a sidewall instead of waiting for access to the tunnel face.…”
Section: Discussionmentioning
confidence: 99%